(untitled) (Minerva. Revista de Filología Clásica, 2019)
This paper refers to the consideration of Roman Law in 18th and 19th centuries, especially by the German Historical School and Pandectists, that took the Corpus Iuris Civilis as a practical legal system and tried to follow the path of the Roman classical jurists, whose historical role and main activities are here summarised.